Fear of Cancer Recurrence Associated with Perceived Cognitive Impairment among Women with Cancers: Findings from the Women’s Health Initiative Life and Longevity After Cancer Study - Yesol Yang; Eric M. McLaughlin; Michelle J. Naughton; Diane Von Ah; Nazmus Saquib; Judith E. Carroll; Lihong Qi; Dorothy S. Lane; Tonya S. Orchard; Electra D. Paskett (Preventive Oncology & Epidemiology)
Background: Perceived cognitive impairments(PCI) are the most common complications that Non-Central Nervous System (Non-CNS) cancers survivors experience. Studies have suggested that those who expreience fear of cancer recurrence (FCR) tend to report cognitive problems; however, this association has not been examined.Methods: Participants (n = 6,714) were enrolled in the Women’s Health Initiative Life and Longevity After Cancer study. FCR was assessed using the Cancer Worry Scale and PCI was assessed using the PCI subscale of FACT-Cog. The association between FCR and PCI was analyzed using univariable and multivariable logistic regression models. A cut off score of [Formula: see text] 14 is indicative of high FCR and below 14 indicating low FCR. Scores lower than 60 indicated PCI.Result: The multivariable model showed that higher FCR corresponded to an increase in odds of PCI (OR = 1.15, p<0.001). We also found that older age at diagnosis (p<0.001), less social support (p = 0.01), over ten pounds of weight gain after cancer treatment (p = 0.02), and mild or worse anxiety (p<0.001) were also associated with increased odds of PCI from the multivariable analysis.Discussion: Our findings indicate that survivors with higher FCR demonstrated poorer cognitive performance than those with lower FCR. These results suggest that those with higher FCR are more likely to report PCI.